Use of video image analysis, ribeye grids, and linear ribeye measurements to predict and compare ribeye areas from carcass left and right sides - Waylan, A.T.; Campbell, R.E.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ribeye tracings from 265 beef carcasses were used to compare ribeye areas from right and left sides. When video image analysis (VIA) was used to determine ribeye area, no difference (P=.48) was observed between right and left sides. However, when ribeye area was determine d by using USDA grids, those on the left side were slightly larger (P<.01) than those on right side. This difference is negligible considering the wide rang e in variation (SD=.68 in2) between right and left side ribeye areas. Ribeye area correlations between VIA and grid result s were high for both right (.96) and left (.95) sides. Linear measures (length, midwidth, and widest width) of ribeyes predicted ribeye area with reasonable accuracy ( R2=.90 and .91). These methods provide several options to determine ribeye area. However, data collectors need to realize that the difference between right and left side ribeye areas may be a greater variable than the sensitivity of the method used.
Keywords: Beef; Video image analysis; Ribeye grids; Linear ribeye measurements